The Effect of Giving Ethanol Extract of Palm Fruit (Arenga pinnata Merr.) on Morphology and Liver Function of White Rats (Rattus norvegicus L.) Induced by Carbon Tetrachloroide - Lubis, Widya Ramadhani; Tambuna, Efrida pima Sari; Syukriah, Syukriah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Carbon tetrachloride is well known as hepatotoxic, including toxic substances commonly used to induce liver damage. Sugar palm (Arenga Pinnata Merr.) is a type of palm plant that is used as a source of antioxidants, one of which is part of the fruit. The aim of this research is to determine the effect of administering ethanol extract of palm fruit (Arenga pinnata Merr.) on the morphology and liver function of rats (Rattus norvegicus L.) which is induced by carbon tetrachloride. This research method used a completely randomized design consisting of 20 mice grouped into 5 groups, namely negative control, positive control, P1 (ethanol extract of palm fruit 90 mg/kg BW), P2 (180 mg/kg BW), P3 (360 mg /kg BW) with each group having four repetitions. Data analysis was carried out using the One Way ANOVA test and continued with the Duncan test. The results of this study show that carbon tetrachloride at a dose of 1 mL/kg BW can damage the morphological appearance of rat liver and increase SGOT and SGPT levels. Giving ethanol extract of palm fruit to the P3 group at a dose of 360 mg/kg BW was the most effective dose to improve liver morphology and reduce SGOT and SGPT levels in white rats induced by carbon tetrachloride.